2012
DOI: 10.1371/journal.pone.0032574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of S-Propargyl-Cysteine (SPRC) in Caerulein-Induced Acute Pancreatitis in Mice

Abstract: Hydrogen sulfide (H2S), a novel gaseous messenger, is synthesized endogenously from L-cysteine by two pyridoxal-5′-phosphate-dependent enzymes, cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE). S-propargyl-cysteine (SPRC) is a slow H2S releasing drug that provides cysteine, a substrate of CSE. The present study was aimed to investigate the effects of SPRC in an in vivo model of acute pancreatitis (AP) in mice. AP was induced in mice by hourly caerulein injections (50 µg/kg) for 10 hours. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…These findings indicated that SPRC could be another protective molecule in MI, and the effects of SPRC are probably mediated by the CSE/H 2 S pathway. Other effects of SPRC, such as anticancer and anti-inflammation, have also been reported Sidhapuriwala et al 2012). …”
Section: 5mentioning
confidence: 96%
“…These findings indicated that SPRC could be another protective molecule in MI, and the effects of SPRC are probably mediated by the CSE/H 2 S pathway. Other effects of SPRC, such as anticancer and anti-inflammation, have also been reported Sidhapuriwala et al 2012). …”
Section: 5mentioning
confidence: 96%
“…Therefore, protective actions of H 2 S-releasing compounds may be caused by an inhibition of endogenous H 2 S formation, possibly by a negative feedback mechanism caused by very low local levels of H 2 S. Another slow H 2 S-releasing drug is S-propargyl-cysteine (SPRC), a structural analog of S-allyl cysteine (SAC) with a common cysteine-containing structure. Pretreatment with SPRC has been shown to protect mice against acute pancreatitis and associated lung injury (Sidhapuriwala et al 2012). Another slow H 2 S-releasing compound is GYY4137 (morpholin-4-ium-4-methoxyphenyl(morpholino) phosphinodithioate), which has been reported to have an anti-inflammatory action (Li et al 2009(Li et al , 2013.…”
Section: H 2 S Donorsmentioning
confidence: 99%
“…For example: lethal hypoxia [3], ischemia/reperfusion (I/R)-injury [430], cardiac arrest [3136], hemorrhage and resuscitation [3745], acute lung injury resulting from blunt chest trauma [46,47] and/or injurious mechanical ventilation [4850], as well as systemic inflammation resulting from endotoxin injection [5159], acute pancreatitis [6063], polymicrobial sepsis [6470], and/or burn injury [7173]. While the beneficial effect of exogenous H 2 S supplementation and maintaining endogenous H 2 S production, respectively, are well-established in I/R injury, equivocal results were reported after cardiac arrest, hemorrhage and resuscitation, and, in particular, in sepsis: inhaling gaseous H 2 S [33,44,48,50,53,54,65], the injection of the sulfide-containing salts NaSH [31,39,49,51,59,63,64,6671,120] and Na 2 S [32,3438,41,42,44,47,48,72,73] or the slow-releasing H 2 S donor GYY4137 [55] as well as of inhibitors of H 2 S production [43,45,5860,62,63,6771,120] were associated with attenuation of shock-related organ dysfunction. Consequently, knowledge about vascular sulfide concentrations may assume major importance, in particular in the context of “ acute on chronic disease ”, i.e., during circulatory shock in animals with pre-existing chronic disease, which per se may markedly alter endogenous H 2 S production, e.g., atherosclerosis [74], arterial hypertension [75,76], chronic kidney disease [77,78], and/or chronic obstructive pulmonary disease (COPD) [7981].…”
Section: Introductionmentioning
confidence: 99%